Pengaruh Tingkat Pengungkapan Informasi Korporasi Berbasis Website Terhadap Perilaku Tax Avoidance Perusahaan Go Public di Indonesia - Fadhila Purendka; Liza Alvia; Mega Metalia; Neny Desriani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to determine the effect of the level of website-based disclosure of company information on corporate tax avoidance behavior. The objects in this research are all companies listed on the Indonesia Stock Exchange for the period June 2024. Data collection in this research uses content analysis methods and data processing using the SPSS application. The sampling technique in this research used purposive sampling with a final sample size of 399 companies. The research results show that the level of website-based disclosure of company information has a negative and significant effect on tax avoidance behavior in public companies in Indonesia.